Human subjectivity and technology in Richard Morgan’s altered carbon - Shahizah Ismail Hamdan, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
This paper looks at human subjectivity as it interfaces with technological advancements portrayed in ‘Altered Carbon’, a contemporary Science Fiction novel. The term subjectivity, in this paper, is used synonymously with identity and the sense of self. The concepts reflect human existence that is in constant negotiation with the environment and embodiment. The analysis looks at how and why the mind/body, a basis of human subjectivity but considered as two different entities, are changed or altered due to interfacings with technologies. Through portrayals in the genre of Science Fiction, this paper envisions the shape of future subjectivity. Though this study does not attempt to provide an authoritative or conclusive charting of human subjectivity, it serves to provide an insight into our evolution to becoming posthumans as a result of our close contact with technology, as seen through the imagined worlds of Science Fiction.